Predicting Severity of Coronary Artery Disease in Patients With Diabetes Using Endothelial Function Measured With Peripheral Arterial Tonometry: PROCEED Study. (August 2019) - Venuraju, Shreenidhi; Jeevarethinam, Anand; Mehta, Vishal Shahil; Ruano, Sherezade; Dumo, Alain; Nair, Devaki; Rosenthal, Miranda; Darko, Daniel; Cohen, Mark; Rakhit, Roby; Lahiri, Avijit
Endothelial dysfunction is common in patients with type 2 diabetes mellitus (T2DM) and is associated with atherosclerotic disease. This study aimed to determine prognostic factors for endothelial dysfunction and identify relationships between reactive hyperemia index (RHI) score, clinically relevant coronary artery disease (>50% stenosis), and major adverse cardiovascular events (MACEs) in patients with T2DM. Endothelial function was assessed using peripheral arterial tonometry and correlated with patient characteristics and cardiovascular outcomes during a median follow-up of 22.8 months. Among 235 patients with a median duration of T2DM of 13 years, mean (standard deviation) RHI score was 2.00 (0.76). Serum low- and high-density lipoprotein cholesterol levels positively ( P = .004) and negatively ( P = .02) predicted RHI score, respectively. Median coronary artery calcium (CAC) score was 109 Agatston units, but no correlation between CAC and RHI scores was observed. The RHI score did not predict the number or severity of coronary plaques identified using computed tomography coronary angiography. Additionally, there was no association between RHI score and the risk of an MACE during follow-up. Overall, endothelial function was not predictive of CAC score, extent, and severity of coronary plaque or MACEs and did not demonstrate utility in cardiovascular risk stratifying patients with T2DM.